A new robust image watermarking approach using two-level intermediate significant bits coupled with histogram intersection technique [electronic resource] - Mir Shahriar Emami, 1970- (2012)
Thesis (Ph.D (Sains Komputer)) - Universiti Teknologi Malaysia, 2012